Comparison of Spheroidal Carbonaceous Particle Data with Modelled Atmospheric Black Carbon Concentration and Deposition and Air Mass Sources in Northern Europe, 1850–2010 - Meri Ruppel; Marianne T. Lund; Henrik Grythe; Neil L. Rose; Jan Weckström; Atte Korhola (Advances in Meteorology)
Spheroidal carbonaceous particles (SCP) are a well-defined fraction of black carbon (BC), produced only by the incomplete combustion of fossil fuels such as coal and oil. Their past concentrations have been studied using environmental archives, but, additionally, historical trends of BC concentration and deposition can be estimated by modelling. These models are based on BC emission inventories, but actual measurements of BC concentration and deposition play an essential role in their evaluation and validation. We use the chemistry transport model OsloCTM2 to model historical time series of BC concentration and deposition from energy and industrial sources and compare these to sedimentary measurements of SCPs obtained from lake sediments in Northern Europe from 1850 to 2010. To determine the origin of SCPs we generated back trajectories of air masses to the study sites. Generally, trends of SCP deposition and modelled results agree reasonably well, showing rapidly increasing values from 1950, to a peak in 1980, and a decrease towards the present. Empirical SCP data show differences in deposition magnitude between the sites that are not captured by the model but which may be explained by different air mass transport patterns. The results highlight the need for numerous observational records to reliably validate model results.